2018
DOI: 10.3390/min8120556
|View full text |Cite
|
Sign up to set email alerts
|

Zircon Xenocrysts from Cenozoic Alkaline Basalts of the Ratanakiri Volcanic Province (Cambodia), Southeast Asia—Trace Element Geochemistry, O-Hf Isotopic Composition, U-Pb and (U-Th)/He Geochronology—Revelations into the Underlying Lithospheric Mantle

Abstract: Zircon xenocrysts from alkali basalts in Ratanakiri Province, Cambodia represent a unique low-Hf zircon within a 12,000 km long Indo-Pacific megacryst zone. Colorless, yellow, brown, and red crystals ({100}, {101}, subordinate {211}, {1103}), with hopper growth and corrosion features range up to 20 cm in size. Zircon chemistry indicates juvenile, Zr-saturated, mantle-derived alkaline melt (Hf 0.6-0.7 wt %, Y <0.2 wt %, U + Th + REE (Rare-Earth Elements) < 600 ppm, Zr/Hf 66-92, Eu/Eu* N~1 , positive Ce/Ce* N , … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 100 publications
(158 reference statements)
2
12
0
Order By: Relevance
“…Although zircon megacrysts may be potentially derived from carbonatitic, metasomatized mantle material and do not primarily relate to alkali basalts, the zircon ages obtained were consistent with bi-episodal eruptive events at Buon Ma Thuot, Dak Lak (5.8-1.67 Ma), Pleiku (4.3-0.8 Ma), and the younger basalt eruptions exposed at Xuan Loc (0.83-0.44 Ma) ( Figure 1B) [4]. Zircon megacrysts from North-East Cambodia not only occur geographically close to the megacrysts found in the present study, but also share a similar U-Pb age connected to the younger period of volcanic activity in the region (0.98 ± 0.04 Ma, Cong et al [10]; 0.88 ± 0.22 Ma to 1.56 ± 0.21 Ma, Piilonen et al [22]). Obtained zircon U-Pb ages were just slightly older than the eruption events that were dated based on the K-Ar ages for the whole rock [4].…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations
“…Although zircon megacrysts may be potentially derived from carbonatitic, metasomatized mantle material and do not primarily relate to alkali basalts, the zircon ages obtained were consistent with bi-episodal eruptive events at Buon Ma Thuot, Dak Lak (5.8-1.67 Ma), Pleiku (4.3-0.8 Ma), and the younger basalt eruptions exposed at Xuan Loc (0.83-0.44 Ma) ( Figure 1B) [4]. Zircon megacrysts from North-East Cambodia not only occur geographically close to the megacrysts found in the present study, but also share a similar U-Pb age connected to the younger period of volcanic activity in the region (0.98 ± 0.04 Ma, Cong et al [10]; 0.88 ± 0.22 Ma to 1.56 ± 0.21 Ma, Piilonen et al [22]). Obtained zircon U-Pb ages were just slightly older than the eruption events that were dated based on the K-Ar ages for the whole rock [4].…”
Section: Discussionsupporting
confidence: 79%
“…Trace-element chemical signatures of the zircon megacrysts of south-central Vietnam were found to be very comparable to those of zircon from Ratanakiri, Northeast Cambodia (Figure 7 in Cong et al [10]; Figure 7 in this study) and other places such as New Zealand [11], East Australia [18], eastern and northeast China [5,8]. Results of a detailed study by Cong et al [10] and Piilonen et al [22] using δ 18 O and 176 Hf/ 177 Hf isotopes clearly demonstrated that zircon from Ratanakiri, Cambodia, had a mantle origin and may be derived from metasomatized, partially melted lithospheric mantle material (such as peridotite, harzburgite), with strong carbonatitic geochemical fingerprint. In fact, experimental studies by Foley et al [51], have demonstrated that mantle metasomatism, as induced by the presence of CO 2 and H 2 O, lowers the solidus temperature at upper mantle conditions and promotes partial melting of the peridotites that results in melts with carbonatitic compositions at low degree, and carbonated silicate melts with higher degrees of melting.…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…Zircon is another important mineral geologically [27,28], which can be of gem-quality. Studies on gem-quality zircons from two occurrences are also included in this Special Issue [29,30]. Data by Piilonen et al [29] on zircon xenocrysts from alkali basalts in Ratanakiri Province (Cambodia) suggest that their genesis involved zirconium-saturated, aluminium-undersaturated, carbonatitic-influenced, low-degree partial melting (<1%) of peridotitic mantle at ca.…”
mentioning
confidence: 99%